Clinical Manifestations and Distribution of Treatment for Pyoderma at a Tertiary Hospital in Surabaya, Indonesia - Auliya, Arsya; Astari, Linda; Puspitasari, Dwiyanti; Alinda, Medhi Denisa (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Pyoderma is a skin disease caused by infection with Gram-positive bacteria. In Indonesia, this disease has a high prevalence due to inadequate sanitation, climate condition, humidity, and high population density. Patients with pyoderma present in diverse range of symptoms, in the form of clinical manifestation or systemic symptoms. Inadequate management of pyoderma can lead to an escalation in morbidity rates. Therefore, it is important to conducting comprehensive research about clinical profile of pyoderma patients. Purpose: To describe the profile of pyoderma patients in Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Acdemic Hospital Surabaya in January 2016 to December 2018. Methods: This study is a retrospective descriptive analysis using secondary data derived from medical records at Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Academic Hospital Surabaya. Result: The analysis of pyoderma patient at Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Academic Hospital Surabaya in January 2016 to December 2018 reveals a total of 407 patients, predominantly male and the most age category were toddlers. Most clinical diagnosis were furuncles and carbuncles. Among the clinical manifestations, macula was the most frequent primary skin lesion, while erosion predominated among secondary lesions. The most commonly administered therapies were systemic and topical antibiotics. Conclusion: In the period from January 2016 to December 2018, clinical manifestations of pyoderma patients at the Dermatology and Venereology Outpatient Unit of Dr. Soeto...